ANALISIS PERSEPSI DAN MINAT MAHASISWA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH TERHADAP PROFESI GURU - Muslimah Nurmadani, Fatihatun; Humaeroh, Iis; Utami, Dewi (Sindoro: Cendikia Pendidikan, 2024)
The background of this research relates to the perceptions and interests of students in the Madrasah Ibtidaiyah Teacher Education Program at the Al-Zaytun Islamic Institute of Indonesia towards the teaching profession. Students' perceptions of this profession include views on the role of teachers as dedicated mentors and unsung heroes who provide education and shape the character of young generations. The students' interest in becoming teachers arises from several motivations, both intrinsic and extrinsic, such as a desire to contribute to the field of education and support from their environment. The research findings indicate that positive perceptions and strong interest correlate with students' aspirations to pursue a career in teaching, with family background, learning experiences, and teaching practice as influencing factors. This research aims to analyze the perceptions and interests of students in the Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program at the Al-Zaytun Islamic Institute of Indonesia towards the teaching profession. The research uses a qualitative approach, with a Random Sampling method, and employs observation, interviews, and documentation to collect data from PGMI students. The data collection technique involves using data triangulation to ensure the validity of the data used by the researcher. The research findings indicate that students' perceptions of the teaching profession are influenced by internal factors such as personal interest and encouragement from family, as well as external factors like perceptions of the welfare and challenges of the teaching profession. Most students have a high interest in becoming teachers due to idealism and a desire to contribute to education, although some also consider the challenges of this profession. The findings of this research are expected to assist educational institutions in improving the quality of teacher education and motivating students to pursue careers as educators. Keywords: perceptions, interests, PGMI students, teaching profession, education.